P308 Continued statural growth In older adolescents and young adults with Crohn's disease and ulcerative colitis beyond the time of expected growth plate closure. (16th January 2018) - Gupta, N; King, E; Liu, C; Sylvester, F; Lee, D; Boyle, B; Trauernicht, A; Chen, S; Pratt, J; Colletti, R; ,
Abstract: Background: Statural growth, a dynamic marker of disease activity, is commonly impaired in paediatric Crohn's disease (CD), not ulcerative colitis (UC). Delayed bone age (BA) is common in CD; its frequency in UC is unknown. Bone age measurements facilitate clinically meaningful interpretation of statural growth. Growth plates close at bone age (BA) 15 years in females (F) and 17 in males (M). Delayed skeletal maturation results in delayed closure of growth plates and continued growth potential. The aim of this study was to determine (1) the frequency of continued growth beyond the time of expected growth plate closure in a large cohort of patients with paediatric CD and UC and (2) the total height gain and years of additional growth after baseline to achieve final adult height in the patients exhibiting continued growth. Methods: We identified all F ≥ chronological age (CA) 15 years and M ≥ CA 17 years with CD and UC in the ImproveCareNow registry who had height documented at ≥3 visits at least 6 months apart. We defined continued growth as height gain ≥1.0 cm after CA 15 years in F 's and 17 in M 's (baseline). Fisher's exact test, Kaplan–Meier estimates, and log-rank tests were utilised. Results: A total of 3011 patients (48% F; 76% CD; 24% UC) met study criteria. See Table for detailed results. A total of 2143 (71%) patients manifested continued growth, which was more common in CD than UC and in CD F 's than CD M 's. In patients who continued to grow, median CA at which final adult height was achieved was 18.8–19.0 years in M 's and 16.9–17.1 years in F 's; median final adult height was 178.6–182.5 cm in M 's and 165.0–166.2 cm in F 's. Median final adult height was greater in UC M's than CD M 's. Median height gain was 2.1–2.5 cm in M 's and 2.1–2.8 cm in F 's. CD F 's achieved greater height gain from baseline that UC F 's. Conclusions: In the largest cohort of older adolescents and young adults with IBD reported to date, our results support that patients with IBD may continue to grow beyond the expected time of growth plate closure. Continued growth is more common in CD than in UC and more common in CD F 's than CD M 's. A novel finding is that a high proportion of patients with UC exhibit continued growth, suggesting delayed BA is common in UC. These data highlight the need for prospective longitudinal studies to examine BA progression and statural growth in patients with CD and UC.